Breaking barriers: a qualitative exploration of healthcare access for crack cocaine users in Limerick - Yaa Asuaba Duopah; Lisa Moran; Khalifa Elmusharaf; Dervla Kelly (BMC Health Services Research)
Abstract Background of study Crack cocaine use in Ireland began to emerge as a significant problem in the early 2000s, with prevalence increasing from 2016 onwards. Services such as harm reduction, treatment/rehabilitation, primary healthcare and social services are available to crack cocaine users in Ireland. However, research addressing specific barriers to accessing these services remains limited. Internationally, while research on healthcare access barriers for crack cocaine users exists, it predominantly focuses on user perspectives. This paper uses a dual-perspective approach to investigate access challenges from both service user and service provider viewpoints, promoting a more patient-centred, holistic approach to service provision. Methodology The study is qualitative and used semi-structured interviews and a focus group to obtain study data. Levesque’s conceptual framework for healthcare access underpins this study. Data were analysed using thematic analysis. Results The study highlighted barriers to healthcare access such as the inadequacy of services to support those with dual diagnosis. However, an advancement has been made through the establishment of specialised dual diagnosis teams and community dual diagnosis services in Ireland. Stigma from health care providers further hindered people from seeking help, highlighting the significance of ongoing efforts in Ireland to address stigma. Systemic factors such as distrust in services, stringent requirements and insufficient knowledge of user needs hamper timely access to care, underlining the need for more adaptive responses. Conclusion The study underlines the need for a tailored approach to enhancing access to health care for crack cocaine users in Ireland. Facilitating collaboration among health care providers, fostering partnerships with educational institutions/communities, and implementing policy changes are essential in creating a supportive environment that promotes help-seeking in Ireland.